Quality of Life Analysis During Transition From Stationary to Portable Infusion Pump in Home Parenteral Nutrition Patients: A Canadian Experience. (February 2014) - Saqui, Olivia; Fernandes, Gail; Allard, Johane P.
Background: Quality of life (QOL) of patients receiving home parenteral nutrition (HPN) may be impacted by device technology. Historically, our HPN patients used pole-mounted pumps which can hinder activities and affect QOL. Methods : Patients receiving HPN with a pole-mounted pump completed Short Form 36 (SF-36®) and pump-specific questionnaires. Patients were then enrolled in a 2-month prospective crossover open study. Patients were randomized to use a pole-mounted pump or a portable pump. After 1 month, each arm crossed over. Measurements were repeated at 4 and 8 weeks. Results : Participants included 5 males, 15 females; age 52.8 ± 3.3 (mean ± SEM) years; 50% had short bowel syndrome; received HPN for 83.3 ± 15.9 months; infused HPN over 11.2 ± 0.3 hours/day; 4.3 ± 0.4 days/week. Portable pump users scored 53.75 ± 5.64, 61.25 ± 6.14, and 40.31 ± 4.94 in SF-36v2 physical, social, and health vitality, respectively, while the stationary pump users scored 45.50 ± 4.82, 55.00 ± 5.97, and 35.31 ± 4.63, respectively (NS). They reported ease of movement between rooms (4.11 ± 0.21 vs 1.44 ± 0.20; P = .001); when traveling (5.00 ± 0.00 vs 3.00 ± 0.45; P < .02) (1 = very difficult, 5 = very easy ); 5.0% were sleep disturbed with the portable compared to 42.1% with pole-mounted pump ( P < .04). Overall, patients were significantly happier with the portable vs pole-mounted pump (4.53 ± 0.19 vs 2.68 ± 0.22; P < .001) (1 = very unhappy, 5 = very happy ). Conclusion : Our HPN patients reported improved happiness and satisfaction regarding ease of use and function with a portable vs pole-mounted pump